Beyond the classroom: How CSR fosters teacher well-being and institutional success in higher education - Yansen Che; Sarminah Samad; Heesup Han; Hyungseo Bobby Ryu (Acta Psychologica)
This study examines the effect of corporate social responsibility (CSR) on teacher well-being in the higher education sector, highlighting the mediating roles of communal relationships and teacher admiration and the moderating effect of teacher altruism. Data from 472 university teachers across six higher education institutions in Beijing, Shanghai, and Guangzhou (China) were analyzed using structural equation modeling. Results indicate that CSR positively affects teacher well-being both directly and indirectly via stronger communal relationships and increased teacher admiration. Teacher altruism further strengthens the positive CSR–admiration link but does not significantly influence the CSR–communal relationships link. The findings suggest that aligning CSR initiatives with faculty values maximizes positive outcomes for staff. The study offers theoretical implications by supporting the Conservation of Resources framework in an educational context and extends CSR research into the higher education sector. It also provides practical recommendations for university administrators to develop CSR strategies that promote a supportive and fulfilling environment for educators.